PENERAPAN METODE TIME AND MATERIAL PRICING SEBAGAI DASAR PENENTUAN HARGA JUAL JASA PADA PT. SINAR GALESONG MANDIRI MALALAYANG MANADO - Lolong, Enjelin; Ilat, Ventje; Tirayoh, Victorina (Universitas Sam Ratulangi, 2019)
Determination of selling prices can be done with several approaches, one of which is the cost approach can identify the amount of costs that have been incurred to produce a product or service. This research was conducted at PT. Sinar Galesong Mandiri Malalayang Manado having its address at Malalayang, North Sulawesi. The purpose of this study is to apply the Time and Material Pricing Method in determining the selling price of services in the workshop of PT. Sinar Galesong Mandiri Malalayang Manado. The method of analysis uses quantitative descriptive data analysis methods, described direct costs and indirect costs, as well as analyzing and comparing a situation so that conclusions can be drawn which include the application of the Time and Material Pricing Method as a basis for determining selling prices. The results of the study illustrate that the selling price set by PT. Sinar Galesong Mandiri Malalayang Manado for the workshop is still not appropriate, because in the calculation of the selling price of the service does not take into account the costs incurred by the company. Selling price of the service, so that the price is relatively cheap, will later increase the motor entry unit and will also increase sales volume.